Expression, purification, cocrystallization and preliminary crystallographic analysis of sucrose octasulfate/human complement regulator factor H SCRs 6-8. - Prosser, B; Johnson, S; Roversi, P; Clark, S; Tarelli, E; Sim, R; Day, A; Lea, S (2007)
Human plasma protein complement factor H (FH) is an inhibitor of the spontaneously activated alternative complement pathway. An allotypic variant of FH, 402His, has been associated with age-related macular degeneration, the leading cause of blindness in the elderly. Crystals of FH domains 6-8 (FH678) containing 402His have been grown in the presence of a polyanionic sucrose octasulfate ligand (an analogue of the natural glycosaminoglycan ligands of FH) using both native and selenomethionine-derivatized protein. Native data sets diffracting to 2.3 A and SeMet data sets of up to 2.8 A resolution have been collected. An anomalous difference Patterson map reveals self- and cross-peaks from two incorporated Se atoms. The corresponding selenium substructure has been solved.